Medicinska informatika danes in jutri - Dimec, Jure (Zdravniški vestnik, 2004)
The article describes the state and some trends in the development of medical informatics especially regarding the fields of scientific information, knowledge discovery in databases, and the role of standards in data exchange. The ways of publication of scientific documents experienced dramatic changes with the development of the www, hence causing major changes in daily information practice. Contemporary textual databases contain full documents ofhypertextual and multimedia nature and links to full documents are increasingly common within the records of bibliographic databases. The last decade brought the advent of the web information tools, from web portals to global search engines, which are powerful aids but demand strong precaution regarding the quality of retrieved documents from the users. On the other hand, we are witnessing the development of digital libraries of scientific documents as a result of the self-organization of academic institutions, research groups and individuals, often in the opposition to the interests of publishing companies. The information support as an important element of medical procedures made possible the exchange of data between all segments of the health-care system and it has become clear that lack of standards governing structure, understanding and safety is among the biggest obstacles to successful data exchange. In addition, the article comprises a report on the methods of knowledge discovery in databases, which help us discover hiddenstructures and potential knowledge, invisible to the normal data processing software, in the enormous amount of data.
Keywords: baze podatkov; Computer Communication Networks; Databases, Bibliographic; health care; informatika; information science; informiranje; Medical Informatics; Medical Informatics Applications; Medical Informatics Computing; Medicinska informatika; Medicinska informatika računalniška; Medicinska informatika, aplikacije; Računalniške mreže; standardi; Zbirke podatkov bibliografske; zdravstvo